2009
DOI: 10.1097/pas.0b013e3181ae29d6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Venous Invasion by Elastica van Gieson Stain and Tumor Budding Predicts Local and Distant Metastases in Patients With T1 Stage Colorectal Cancer

Abstract: Evaluation of pathologic predictors of metastases in T1 stage colorectal cancer may be difficult with hematoxylin and eosin (HE) staining alone. The aim of this study was to clarify the role of pathologic predictors by using immunohistochemical staining and Elastica van Gieson (EVG) staining. One hundred and twenty-four patients who underwent bowel resection for single T1 stage colorectal cancer from 1990 to 2004 in 1 institution were studied. D2-40, EVG staining, and CAM5.2 were used to detect lymphatic invas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
92
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 116 publications
(97 citation statements)
references
References 31 publications
(54 reference statements)
2
92
1
1
Order By: Relevance
“…There is a strong association between budding and the presence of lymph node metastases and lymphovascular invasion, 11,12,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] defined by the presence of tumor cells within an endothelium-lined space, and it has been suggested that buds represent the part of the tumor that has gained the ability to invade lymphatics and vascular channels. This idea is supported by two intriguing morphological studies: Morodomi et al 33 examined serial sections of high-budding areas to demonstrate that budding nests are often found adjacent to areas of lymphovascular space invasion, and, in a more recent study, Ohtsuki et al 31 performed double staining for anti-cytokeratin antibodies and anti-lymphatic antibodies, finding that a number of 'buds' at the invasive edge of a tumor are in fact located in small lymphatic spaces.…”
Section: Morphological Featuresmentioning
confidence: 99%
See 4 more Smart Citations
“…There is a strong association between budding and the presence of lymph node metastases and lymphovascular invasion, 11,12,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] defined by the presence of tumor cells within an endothelium-lined space, and it has been suggested that buds represent the part of the tumor that has gained the ability to invade lymphatics and vascular channels. This idea is supported by two intriguing morphological studies: Morodomi et al 33 examined serial sections of high-budding areas to demonstrate that budding nests are often found adjacent to areas of lymphovascular space invasion, and, in a more recent study, Ohtsuki et al 31 performed double staining for anti-cytokeratin antibodies and anti-lymphatic antibodies, finding that a number of 'buds' at the invasive edge of a tumor are in fact located in small lymphatic spaces.…”
Section: Morphological Featuresmentioning
confidence: 99%
“…Similarly, the presence of budding has been associated with increased risk of distant metastases, [34][35][36] suggesting that budding may also be associated with vascular invasion. A few tumor-budding studies have used vascular markers and/or elastic stains to assess vascular invasion, 11,12,19,22,26,32,37,38 but only four have analyzed the relationship between budding and vascular invasion: Kazama et al 22 found no relationship between budding and vascular invasion, whereas three other studies have reported a statistically significant correlation between budding and venous invasion, though the association was not as pronounced as the relationship with lymphatic invasion and lymph node metastases. 11,12,32 The tumor-host interaction at the invasive front may be of prognostic importance in the setting of tumor budding.…”
Section: Morphological Featuresmentioning
confidence: 99%
See 3 more Smart Citations